The role of Nursing in enhancing patient care: A comprehensive review - Abdulwahab Alghanim, Abdulrahman; aldowban, Ibrahim Mohammed; almutairi, Haggad Bajjad; Saud Alsarami, Abdulhakim; alhammad, Abdulaziz saleh; Al absi, Fatemah Ali; Alsbahn, Faisal Abdullah (Journal of Neonatal Surgery, 2026)
Nursing is a cornerstone of health systems in diverse countries all over the world functioning as a key interface between patients and an ever-complicated medical care. The profession of nursing has over time evolved to include more than just the traditional bedside care to entail more aspects such as advanced clinical judgement, patient advocacy, health promotion, and evidence-based practice. The long-term presence of nurses in the variety of care environments helps them to meet the clinical and psychosocial needs of patients, which creates a powerful impact on the health outcomes, safety, and patient satisfaction. The reason behind this review is the changing and complex nature of the roles of nursing across the health care continuum, which include acute care, chronic disease management, preventive services, and emergency response. It outlines the role of modern nursing in quality improvement, efficiency, and patient-centered care in hospitals, community settings, and the public health settings. Health-care organizations and policymakers aiming to maximize the delivery of services and attain sustainable improvements in global health outcomes must have a comprehensive understanding and fortification of the nursing role...